UNO, NESSUNO, CENTOMILA. QUALE ITALIANO INSEGNARE NELL’ERA DIGITALE? (Journal of Foreign Language Studies, 2023)
This study discusses sociolinguistic variation in the Italo-Romance languages, with special attention to neo-standard Italian and its diffusion. First, the study presents the diversity of this group of languages (including standard Italian, Italaiuan regional varieties, dialects, and new immigrant languages) as well as their relations among individual and community languages. It then discusses some variation related to third person clitic pronouns through examples of their use in literary texts. Finally, some thoughts will be devoted to the relevance of variation in teaching Italian as a native and foreign language.
Keywords: sociolinguistic variation; neo-standard Italian; Italian regional varieties; clitic pronoun